Peranan Politik Pendidikan Syekh Ali Hasan Ahmad Addary dalam Mengembangkan Pendidikan di Wilayah Mandailing - Hasibuan, Kholidah Hannum; Hasibuan, Zainal Efendi (CV. Lenggogeni Data Publishing, 2025)
The politics of education, which is essentially efforts and activities that refer to and are relevant to the formation and development of educational policies to achieve effective educational goals, has a close relationship with educational figures in its implementation. In this article, one of the Islamic educational figures who contributed greatly to Islamic learning such as hadith learning is Sheikh Ali Hasan Ahmad Addary, with the aim that the Islamic educational figure can be examined in developing education. This will then be raised in the discussion and review of relevant literature on the object of this article. Qualitative research with a literature review approach is raised in this work as a form of examination of the traces of the contribution of the educational figure Sheikh Ali hasan ahmad addary in developing Islamic education which in this case is centered on the Mandailing region as the base and origin of this Islamic educational figure. Abstrak Politik pendidikan yang pada hakikatnya merupakan upaya-upaya dan kegiatan-kegiatan yang mengacu serta relevan kepada pembentukan dan pengembangan kebijakan pendidikan untuk mencapai tujuan pendidikan yang efektif memiliki kaitan yang erat dengan tokoh-tokoh pendidikan dalam implementasinya. Dalam artikel ini diangkat salah satu tokoh pendidikan islam yang berkontribusi besar dalam pembelajaran keislaman seperti pembelajaran hadis yaitu Syekh Ali hasan ahmad addary, dengan tujuan agar tokoh pendidikan islam itu dapat ditelaah sepak terjangnya dalam mengembangkan pendidikan. Hal ini kemudian akan diangkat dalam pembahasan dan kajian literatur yang relevan akan objek artikel ini. Penelitian kualitatif dengan pendekatan kajian literatur diangkat dalam karya ini sebagai bentuk telaah terhadap jejak kontribusi tokoh pendidikan Syekh Ali hasan ahmad addary dalam mengembangkan pendidikan keislaman yang dalam hal ini dipusatkan pada wilayah Mandailing sebagai basis serta asal dari tokoh pendidikan islam ini. Kata Kunci: politik pendidikan, Syekh Ali Hasan Ahmad Addary, pendidikan, Mandailing